Early identification of functional high-risk multiple myeloma patients after transplant: the predictive power of fat fraction and Response Assessment Category score in diffusion-weighted whole-body magnetic resonance imaging - Angelo Belotti; Barbara Frittoli; Sofia Terlizzi; Rossella Ribolla; Claudia Crippa; Chiara Saeli; Samantha Ferrari; Nicola Bianchetti; Chiara Bottelli; Chiara Cattaneo; Carmela Carbone; Alessandro Gullino; et al. (Haematologica)
Functional high-risk (FHR) multiple myeloma (MM) patients, defined as those with early relapse despite optimal initial therapy, represent an unmet clinical need. Diffusionweighted whole-body MRI (DW-MRI) is increasingly used in MM management due to its high sensitivity in assessing treatment response. The Myeloma Response Assessment and Diagnosis System (MY-RADS) established the Response Assessment Category (RAC), a 5-point scale ranging from complete response (RAC 1) to progressive disease (RAC 5), which independently stratifies patients with different outcomes after autologous stem cell transplantation (ASCT). The relative Fat Fraction (rFF), derived from DW-MRI, provides additional prognostic insights into bone marrow composition. This study aimed to evaluate whether the combined assessment of RAC and rFF could identify FHR MM patients at risk of early relapse, defined as progression within 18 months post-ASCT. Ninety-seven MM patients were retrospectively analyzed after ASCT, before maintenance, with a median follow-up of 47 months. An rFF threshold of 17.2% predicted early relapse with 83% sensitivity and 85% specificity. Patients with rFF >17.2% had significantly improved post-ASCT progression-free survival (PFS, median not reached vs. 13.7 months, HR 0.18; 95% CI 0.08–0.43) and overall survival (OS, 3-year rate: 96% vs. 62%, HR 0.12; 95% CI 0.03–0.45) compared to rFF ≤17.2%. Patients with RAC 1/rFF High had the best outcomes, while RAC ≥2/rFF Low had the worst prognosis (median PFS: NR vs. 12.3 months, HR 0.21; 95% CI 0.07–0.62). rFF complements RAC for response assessment after ASCT, enabling early identification of FHR patients with poor prognosis.